Supercritical Fluid and Cocrystallization Technologies for Designing Antimicrobial Food Packaging Pla Nanocomposite Foams Loaded with Eugenol Cocrystals with Prolonged Release - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Velasquez, E; Catalan-Gamonal, L (Elsevier B.V., 2024)
Searching for effective strategies to modify the release rate of essential oil derivatives is one of the main challenges in designing prolonged-release antimicrobial food packaging materials. Herein, supercritical fluid technology and cocrystallization engineering were used to develop novel eugenol (EU) prolonged-release poly (lactic acid) (PLA) nanocomposite foams. Eugenol-phenazine (EU-PHE) cocrystals, produced by a solvent-free mechanochemical method, were incorporated by supercritical solvent impregnation (SSI) inside PLA nanocomposite foams with different contents of Cloisite30B® (C30B). The effect of the cocrystallization process and C30B content on the EU release kinetics and its relation with their antimicrobial activity by direct contact (anti-attachment) and release in broth culture were studied. The deposition of isolated spherical-shaped micrometric EU-PHE cocrystal particles with 0.8 µm average diameter inside the pores of PLA foams was evidenced by XRD, SEM, DSC, and TGA analyses. The release mechanism of EU and its cocrystal was defined as a quasi-Fickian diffusion process successfully described by the Korsmeyer-Peppas model with release rate constants up to 3.6-fold lower than the release rate constant of pure EU. The impregnated foam samples completely inhibited the attachment of Listeria monocytogenes and Salmonella Enteritidis and provided prolonged antimicrobial activity in broth culture against both food-borne pathogens. This study suggests a new, environmentally friendly method for designing prolonged-release antimicrobial food packaging materials. © 2023 Elsevier B.V.